The role of UNCITRAL in regulating e-contract in the emerging e-commerce - Mohd Shariff, Roos Niza (2006)
ICT and the Internet is indeed a dynamic nature that are constantly changing and moving at a fast pace.In this environment, e-commerce has become a dominant factor in commercial transactions and business arrangements. This is a multimedia environment encompassing borderless, intangible, faceless and metaphysical world that defies traditional concepts of space and time.It converges computing, broadcasting and telecommunication with interactive capabilities. Along with the cross-border communication and global economy, is the arising of legal issue such as e-contract, that is, contracts entered into by parties via the digital networks.This paper is a study of the role of legislative implementation, in particular, the United Nations Commission on International Trade Law (UNCITRAL) in regulating e-contract in the emerging e-commerce.The realm of e-contract specifies the contracting parties dealing in a cyberspace situation.The circumstances surrounding on-line agreement (or e-contract) vary vastly to the paper-based contract function, which sometimes become a barrier to e-commerce transactions.The UNCITRAL is set up to harmonise legal contracting issues arising from contracts entered via electronics medium.Thus, this study is essential in this unchained globalisation environment.The relation between contract, e-contract, e-commerce and e-commerce law are defined before specifying legal issues pertaining to e-commerce which regulates e-contract. After a brief definition and introduction of the UNCITRAL, the main highlights will be on the role of the UNCITRAL in order to see whether it is bridging or creating the gaps between the laws of e-commerce between states and its effects on e-contract.